Reduced Overshoot of The Electroforming Jewellery Process Using PID - Utomo, Arie Cahyo; Siwindarto, Ponco; Setyawati, Onny (Universitas Muhammadiyah Malang, 2020)
The electroforming jewellery is the electrodeposition process of coating metal on an insulator object to make a jewellery product. The problems are burnt and uneven results in their products, it happened because electrical currents while the process increased. So, too many metal particles attached to object. The problems of electroforming process can fix with a control system, where controller must makes constant electrical currents while the process. In this paper, the problems was changed to the equation by the polynomial regression method as a plant. Secondly the characteristic of current sensor was found by the linier regression method as a feedback system. The system used buck converter as the actuator, where it was written to the equation by the state space method. The controller was chosen by comparison 4 types controller, they are a conventional controller, proportional controller, proportional – integral (PI) controller, and proportional – integral – derivative (PID) controller. Xcos Scilab used to simulated the system and got the system with a proportional – integral – derivative controller is the best controller. The system with a proportional – integral – derivative controller have a Rise time 1.3687 Seconds and Overshoot 2.5420%. The result of research will be base to makes hardware system where it will help the advancement of the creative economy industry in Malang City.